Rapid en-bloc hematoxylin-eosin staining for human lung cancer tissue for fluorescence micro-optical sectioning tomography - Ding, Yun; Wei, Huaye; Liu, Xin; Xu, Meilin; Sun, Daqiang; Li, Ting; Li, Xin (Frontiers in Physics, 2023)
Objective: To establish a rapid and effective method for en-bloc hematoxylin-eosin (HE) staining and paraffin embedding of human lung cancer and paracancerous tissues which can be applied to fluorescence micro-optical sectioning tomography (fMOST). Methods: Human lung cancer and paracancerous tissues with a size of about 1 cm × 1 cm × 0.3 cm were taken and fixed in 10% neutral formalin. HE staining was performed using a heat water bath to facilitate staining. After staining, isopropyl alcohol was used for dehydration and transparency. Then, 65℃ paraffin was used for wax immersion followed by paraffin embedding, while continuous paraffin sections were produced for observation. Results: The tissues stained by en-bloc HE, dehydrated, transparent and wax immersion were slightly smaller in appearance, darker in color and slightly harder in texture than before. After paraffin embedding, the wax blocks did not show any obvious fragmentation, wrinkling or cavity formation, and could be continuously cut into 4-μm thick slices which could be dragged to form wax tapes. The sections could develop flat in waterbath, and the tissues showed no signs of collapse or separation from the paraffin. After sections were picked up and dewaxed, the tissue structure was intact and the cell structure was clear under light microscopy, which could be used to evaluate the pathological features of lung cancer and paracancerous tissues. Conclusions: We propose a suitable en-bloc HE staining of centimeter-sized lung cancer and paracancerous tissues that can be applied to fMOST. It is promising to be used in the accurate identification of structural landmarks and spatial assessment of lung cancer.